2007
DOI: 10.1038/nchembio.2007.55
|View full text |Cite
|
Sign up to set email alerts
|

An allosteric potentiator of M4 mAChR modulates hippocampal synaptic transmission

Abstract: Muscarinic acetylcholine receptors (mAChRs) provide viable targets for the treatment of multiple central nervous system disorders. We have used cheminformatics and medicinal chemistry to develop new, highly selective M4 allosteric potentiators. VU10010, the lead compound, potentiates the M4 response to acetylcholine 47-fold while having no activity at other mAChR subtypes. This compound binds to an allosteric site on the receptor and increases affinity for acetylcholine and coupling to G proteins. Whole-cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
163
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(178 citation statements)
references
References 42 publications
14
163
1
Order By: Relevance
“…M 4 PAMs bind to an allosteric site and can increase both the affinity of M 4 for ACh and the efficiency of coupling of M 4 to G proteins (Shirey et al, 2008). Consistent with their effects in cell lines, M 4 PAMs potentiate M 4 -mediated depression of excitatory synaptic transmission at hippocampal CA1 synapses (Shirey et al, 2008). Chemical optimization of early M 4 PAMs resulted in the discovery of VU0152100 as a centrally penetrant highly selective M 4 PAM .…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…M 4 PAMs bind to an allosteric site and can increase both the affinity of M 4 for ACh and the efficiency of coupling of M 4 to G proteins (Shirey et al, 2008). Consistent with their effects in cell lines, M 4 PAMs potentiate M 4 -mediated depression of excitatory synaptic transmission at hippocampal CA1 synapses (Shirey et al, 2008). Chemical optimization of early M 4 PAMs resulted in the discovery of VU0152100 as a centrally penetrant highly selective M 4 PAM .…”
Section: Introductionmentioning
confidence: 89%
“…These efforts have led to the discovery of highly selective M 4 positive allosteric modulators (PAMs) that do not activate M 4 directly, but markedly potentiate the response of M 4 to ACh (Shirey et al, 2008;Chan et al, 2008;Brady et al, 2008). M 4 PAMs bind to an allosteric site and can increase both the affinity of M 4 for ACh and the efficiency of coupling of M 4 to G proteins (Shirey et al, 2008). Consistent with their effects in cell lines, M 4 PAMs potentiate M 4 -mediated depression of excitatory synaptic transmission at hippocampal CA1 synapses (Shirey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides novel insights into the molecular mechanisms of action of LY2033298, which, together with a related series of molecules, has recently been proposed as a novel, M 4 -mAChR-selective, tool that may provide a new avenue for the treatment of disorders such as schizophrenia (Chan et al, 2008;Shirey et al, 2008). We have defined a mechanistic basis for the differential effects of this compound on the binding of orthosteric antagonists compared with agonists such as ACh, have validated pharmacologically that both agonism and modulation by LY2033298 arise from an allosteric site that likely overlaps with the site used by prototypical mAChR modulators, have identified, for the first time, signal pathway-selective allosteric modulation at the M 4 mAChR, and validated this receptor subtype as a key target for LY2033298 in native cellular systems as well as in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…6, the inhibitory manner of MT3 in the present study was inconsistent with the typical competitive antagonism shown in the mAChRmediated adenylate cyclase inhibition assay in rat striatal (33) (36). Among them, VU 10010 is particularly useful in investigations of M 4 mAChRs because this compound has been shown to act as a highly selective allosteric potentiator at the M 4 subtype with no activity at any other mAChR subtypes (9). In the present study, VU 10010 potentiated the effects of CCh, by leftward shifting of the concentration-response curve as well as by enhancing the maximal response.…”
Section: Discussionmentioning
confidence: 42%